If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -5 = 8x + 12 Reorder the terms: -5 + 6x = 8x + 12 Reorder the terms: -5 + 6x = 12 + 8x Solving -5 + 6x = 12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -5 + 6x + -8x = 12 + 8x + -8x Combine like terms: 6x + -8x = -2x -5 + -2x = 12 + 8x + -8x Combine like terms: 8x + -8x = 0 -5 + -2x = 12 + 0 -5 + -2x = 12 Add '5' to each side of the equation. -5 + 5 + -2x = 12 + 5 Combine like terms: -5 + 5 = 0 0 + -2x = 12 + 5 -2x = 12 + 5 Combine like terms: 12 + 5 = 17 -2x = 17 Divide each side by '-2'. x = -8.5 Simplifying x = -8.5
| x=18/2/5 | | x^2+4cx+4=0 | | .3ax=6 | | 8(2p+4)= | | 8(4+2x)= | | x/7=3/14 | | 8x=8x+20 | | -2x-1=3x+5/2 | | -4(-8x+12)=-26-32x | | 5n^2-6=-100 | | Log(7x-100)=3 | | 7d-11=10 | | (v-3)(v-6)=0 | | 2sin(3x)+2sin(x)=0 | | 6s^2-5st+t^2=0 | | Y=8x-100 | | 5n^2-6=-94 | | 100/x=20 | | 3(1-3a)= | | 2-x=5x+4 | | 26-7/8x=2 | | -8x^2+46x+30=0 | | -5(w+7)(-w+2)=0 | | 4x+20=56 | | 48+20=56 | | 3(2x+1)=5x+3 | | (185-2x)+(x-20)=90 | | 4(5-3x)=44 | | 6(-10b+10)= | | X+3-2x=x-7 | | 2(x+3)-13=26+24-1 | | 0=-5/2x-2 |